Railway Dynamics: Global research trends and applications in high-speed railway operation in Vietnam - Nguyen, Huu Phuoc; Ngo, Duy Nam (Tạp chí Khoa học Công nghệ Giao Thông Vận Tải, 2026)
High-speed railway (HSR) systems operating at velocities up to 350 km/h impose stringent requirements on vehicle–track interaction, wheel–rail contact mechanics, and infrastructure maintenance strategies. At such speeds, railway systems behave as highly coupled nonlinear systems. Small variations in contact conditions or track geometry can significantly amplify dynamic responses. This paper presents a comprehensive review of the theoretical foundations of wheel–rail rolling and sliding contact, with particular emphasis on wear and rolling contact fatigue (RCF). Global research trends in railway dynamics are reviewed, highlighting the increasing integration of multibody dynamics (MBD), advanced contact models, and damage prediction techniques. The applicability of these methodologies to the future high-speed railway system in Vietnam is discussed, and engineering-oriented recommendations and parametric considerations are proposed for the development of simulation-based design and predictive maintenance frameworks